CORRELATION STUDIES BETWEEN YIELD AND YIELD ATTRIBUTES OF ELITE RICE GENOTYPES TRANSPLANTED UNDER DIFFERENT GROWING ENVIRONMENTS - and CH. DAMODAR RAJU, SADRAS BHAVANA, T. RAMESH, P. RAGHUVEER RAO, B. BALAJI NAIK (The Journal of Research, PJTSAU, 2021)
The present investigation was carried out at Indian Institute of Rice Research (IIRR) Rajendranagar, Hyderabad to study the direction and degree of correlations between the different parameters of yield attributes and economic yield of 6 elite rice genotypes transplanted under 12 sowing dates that contribute to different growing environment during 2018-19. Character association studies revealed that the parameter grain yield (kg ha-1) showed significant positive association with panicle length, panicle weight, number of filled grains per m-2, grain number per panicle, test weight and spikelet fertility. Therefore, advancement in grain yield is possible by giving emphasis on these characters in selection scheme. Further, the yield attributes were correlated with each other which stated that panicle length was positively influenced by panicle weight and grain number per panicle. Similarly, the panicle weight was positively dependent on filled grain number, grain number per panicle and 1000 grain weight (test weight). The filled grain number was in turn positively impacted by grain number per panicle and 1000 grain weight (test weight). Likewise, the spikelet fertility was positively determined by panicle weight, and test weight. Among the genotypes, the strength and direction of correlation between yield and yield attributes was high and more conspicuous in JGL 3844. Therefore the present investigation clearly inferred that the quantitative traits of most of the yield attributes were contributing to economic yield in different rice genotypes and were highly interdependent.